The Role of Management Information Systems to Increase MSME Sales - Andryan Syaputra (CV. ITTC INDONESIA, 2024)
This study has the goal of finding out how far the Information System functions as a tool to increase product sales in London Fashion Padangsidimpuan. This study uses a qualitative descriptive research methodology. The data sources applied to this study are primary and secondary data sources. The data collection strategy is implemented through the use of observation, interview, and documentation methodologies. The data study in this study includes the data reduction process, data presentation, and conclusions. The results of the study show that the use of Information Systems for promotional media is very significant in boosting product sales (MSMEs) at the London Fashion Padangsidimpuan Store.